2021
DOI: 10.1371/journal.pone.0249407
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias during emotional processing: Behavioral and electrophysiological evidence from an Emotional Flanker Task

Abstract: Threatening stimuli seem to capture attention more swiftly than neutral stimuli. This attention bias has been observed under different experimental conditions and with different types of stimuli. It remains unclear whether this adaptive behaviour reflects the function of automatic or controlled attention mechanisms. Additionally, the spatiotemporal dynamics of its neural correlates are largely unknown. The present study investigates these issues using an Emotional Flanker Task synchronized with EEG recordings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Successfully completing the task relies heavily on WM capacity due to the constant need for updating the information in the WM each time the participant finds the current target (Unsworth & Robison, 2017). Previous studies have shown that the inhibition of emotional stimuli is highly dependent on the availability of WM resources (Schmeichel, 2007; Zanto et al, 2011), but also limits the availability of WM resources to complete the primary task (Schmeichel, 2007; Trujillo et al, 2021; Unsworth & Robison, 2017). It has also been proposed that the facilitating effect of threatening images could be explained by an improved executive control efficiency (Birk et al, 2011); that is, a more efficient allocation of available resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successfully completing the task relies heavily on WM capacity due to the constant need for updating the information in the WM each time the participant finds the current target (Unsworth & Robison, 2017). Previous studies have shown that the inhibition of emotional stimuli is highly dependent on the availability of WM resources (Schmeichel, 2007; Zanto et al, 2011), but also limits the availability of WM resources to complete the primary task (Schmeichel, 2007; Trujillo et al, 2021; Unsworth & Robison, 2017). It has also been proposed that the facilitating effect of threatening images could be explained by an improved executive control efficiency (Birk et al, 2011); that is, a more efficient allocation of available resources.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be in accordance with the pattern that the attentional biases toward threat framework suggests; specifically, that an attentional capture by the threat is followed by a delayed disengagement, ultimately resulting in a hypervigilance-avoidance behavior. Although the hypervigilance-avoidance hypothesis had been initially proposed for phobic populations (Mogg et al, 2004), it has also been shown in nonfearful participants (Berdica et al, 2018; Burra et al, 2019; Trujillo et al, 2021). A recent study (Liesefeld et al, 2017) using salient task-irrelevant distractors (although not emotionally charged ones) proposed a chain of attentional enhancement and suppression mechanisms based on EEG data.…”
Section: Methodsmentioning
confidence: 99%
“…One possible reason for this is that individuals have an attentional bias toward emotions (for a review, see Hu et al, 2018; Van Rooijen et al, 2017). When emotional stimuli appear, people tend to show an acceleration of attentional orientation, and compared with neutral stimuli, emotional stimuli will attract attention and are processed faster (Hu et al, 2018; Trujillo et al, 2021). In the present study, we used pictures of static bodily expressions as the experimental material.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using EEG and fMRI simultaneously while the subjects were viewing visual scenes of pleasant, unpleasant, and neutral content, it was found that a ective scenes, depending on their valence, evoked speci c neural representations (Bo et al, 2021). e in uence of the scene's emotionality on the neuronal response was also shown using evoked potentials (Tebbe et al, 2021;Trujillo et al, 2021). ere was also evidence of valence-modulated susceptibility to the image distortions when observing the scenes (Stevenson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%